Concurrent validity of the Alberta Infant Motor Scale to detect delayed gross motor development in preterm infants: A comparative study with the Bayley III. - Albuquerque, Plínio Luna de; Guerra, Miriam Queiroz de Farias; Lima, Marília de Carvalho; Eickmann, Sophie Helena (Developmental Neurorehabilitation, 2018)
Objective: To investigate the concurrent validity of AIMS in relation to the gross motor subtest of the Bayley Scale III/GM in preterm infants. Methods: A total of 159 gross motor development assessments were performed with the AIMS and Bayley-III/GM. Linear regression was used to assess the correlation between AIMS and Bayley-III/GM scores. The intra-class correlation coefficient (ICC) and the Bland-Altman plot were used to analyze intra- and inter-rater reliability. Results: There was a prevalence of delayed gross motor development of 20.8% according to the Bayley-III/GM, and 11.9% for the 5th percentile and 21.4% for the 10th percentile of AIMS. A good correlation of AIMS with Bayley-III/GM scores and intra- and inter-rater reliability was encountered in this study. Conclusion: AIMS proved very capable of detecting delayed gross motor development in preterm infants when compared with the Bayley-III/GM. The 10th percentile of AIMS provided the best combination of indicators, with greater specificity.